PENGARUH CELEBRITY ENDORSERS DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DAN LOYALITAS PELANGGAN PADA PRODUK PEMBALUT WANITA CHAM BODY FIT DI KOTA BENGKALIS - , Deny Danar Rahayu, Anggi Cakramahe , Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to see how the influence of Celebrity Endorsers and Product Quality on Consumer Satisfaction and Customer Loyalty in Charm Body Fit Sanitary Napkin products in Bengkalis City. The population in this study were women who used and saw Charm Body Fit sanitary napkin advertisements, with a total sample of 112 respondents and the sampling technique used purposive sampling. The data analysis used is Path Analysis with the SPSS program. The results of this study indicate that celebrity endorsers and product quality affect consumer satisfaction and customer loyalty, consumer satisfaction influences customer loyalty, and celebrity endorsers and product quality affect customer loyalty through consumer satisfaction. Keyword : Celebrity Endorsers, Product Quality, Consumer Satisfaction, Customer Loyalty.